CONTRIBUTION OF SOCIAL CAPITAL AND POLITICAL MARKETING TO THE FIGURE OF THE MILLENNIAL GENERATION IN LOCAL POLITICAL CONTESTS IN INDONESIA (Case Study of Muhammad Bobby Afif Nasution's Victory in the 2020 Medan City Pilkada) - Fadli, Teuku Faishal; Aminuddin, M. Faishal; Mashuri, Ali (International Journal of Artificial Intelligence Research, 2024)
This study aims to analyze the political marketing strategy, social capital, and millennial generation of the Bobby and Akhyar pair in the 2020 Medan City Pilkada. This study uses a qualitative case study research method. The research design in this study uses an explanatory case study. The research data consists of primary data and secondary data. The data collection techniques used by the researcher are Documentation, Interviews, and Observation. Based on the results of the study, it shows that the political marketing strategy and social capital carried out by Bobby Nasution as a millennial political actor in the 2020 Medan City Pilkada are by implementing puss marketing (direct meetings with the community), pull marketing (utilizing media in branding his image), pass marketing (utilizing the support of influential figures in campaigning for his political ideas). Bobby Nasution's social capital consists of friendships with influential figures in Medan City, being active as a member of the PDI Party, as the son-in-law of Mr. Jokowi as President of Indonesia and others. The relationship between aspects of political marketing, social capital and millennial political actors in the victory of the Bobby-Aulia pair in the 2020 Medan City Pilkada, namely the victory obtained by the Bobby Nasution pair in the 2020 Medan City Pilkada cannot be separated from the contribution of political marketing carried out, the social capital owned and their brand image as millennial political actors. The three aspects above are interconnected in their implementation, for the ideas and political promises offered will be conveyed through direct meetings with the community, uploaded on social media, forwarded by influential figures, and channeled and assisted by the social capital they have, such as being campaigned by their supporting parties, by their business relations, or by youth communities that are included in the millennial generation community.